Integrating Qur’anic Exegesis and the Johari Window: Toward a Qur’anic Self-Awareness Framework - Nanum Sofia; Misbahul Munir; Yurna Hafizah (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study aims to examine how Qur’anic concepts guide the dynamics of the four quadrants of the Johari Window model and to explore the contribution of a Qur’anic Johari Window model to the development of a more contextual self-awareness framework for muslim communities. Employing a qualitative library research approach, the study analyzes Qur’an 103:3; 61:2–3; 3:159 through a comparative examination of five Qur’anic exegeses and a conceptual dialogue with the Johari Window model. The findings reveal that six Qur’anic concepts demonstrate functional linkages with the dynamics of the four Johari Window quadrants. Shiddiq serves as the ethical foundation of Open Self, tawāṣaw bi al-ḥaqq functions as a mechanism for reducing Blind Spot, tawāṣaw bi al-ṣabr, and ‘afw facilitate openness and trust restoration within Hidden Self, while ‘azm and tawakkul operate complementarily within Unknown Self by encouraging self-exploration and managing uncertainty. Based on this mapping, the study proposes a Qur’anic Johari Window model that preserves the original four-quadrant structure while extending it through normative, relational, and transcendental dimensions. The model offers a more contextual self-awareness framework for muslim communities and provides a conceptual foundation for future empirical research, Islamic counseling, and character education grounded in Qur’anic values.